ISLAMIC ECONOMIC PUBLICATIONS IN THE DEVELOPMENT OF FINANCIAL SYSTEM STABILITY RESEARCH: A BIBLIOMETRIC ANALYSIS - Firmansyah, Irman (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the role of Islamic economic publications in developing research on financial system stability through mapping research results. This research was conducted on journal articles indexed by dimensions.ai from 2017 to 2021. The analysis was carried out by bibliometrics using the R Biblioshiny software. The results show that non-Islamic economic journals dominate the development of journals that publish the theme of financial system stability. There is only one journal that is most relevant to the theme of financial system stability in Islamic economics and is in the top 20, namely